Portrait of Louis XIII of France - Engraving 17th century - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Portrait of Louis XIII of France - Engraving 17th century. Portrait of Louis XIII of France
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons; Iconographie